Research on multi-energy cooperative participation of grid frequency inertia response control strategy for energy storage type doubly-fed wind turbine considering wind speed disturbance - Sun, Dongyang; Zhao, Fanqi; Guo, Yifen; Meng, Fanyi; Zheng, Wenyuan; Yu, Jixuan (Frontiers in Energy Research, 2023)
With the proposal of carbon peaking and carbon neutralization, the penetration rate of wind power generation continues to increase. This paper focuses on the problem that doubly fed induction wind turbines are vulnerable to input “source” disturbances and have weak frequency modulation ability, which reduces the stability of the power grid. Based on the structural model of energy storage system embedded in doubly fed wind power generation system, it is compared the ability of super capacitor energy storage and releasing rotor kinetic energy to provide inertia response power and energy, and the feasibility of multi-energy coordinated inertia response is analyzed. Based on the inertia time constant of conventional synchronous generator set, the inertia time constant and actual inertia constant of energy storage doubly fed wind power generation system under variable wind speed are defined. An extended state observer is used to estimate the change of captured mechanical power caused by the change of wind speed, and a control strategy for doubly fed induction generator with super capacitor to participate in power grid frequency regulation is designed. Finally, considering the aggregation of wind power and the difference of the state of charge during the operation of distributed energy storage, the 3*3*3 wind farm model is established using Matlab/Simulink simulation software. The feasibility and advantages of the frequency modulation control strategy proposed in this paper are verified by building a power grid frequency modulation simulation involving wind farms and traditional generators.